2006
DOI: 10.1385/mo:23:4:489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ERCC1 Polymorphisms and the Modification by Smoking on the Survival of Non-Small Cell Lung Cancer Patients

Abstract: A few reports for ERCC1 SNPs were conducted in patients treated with cisplatin chemotherapy. The aim of this study is to determine whether the SNPs are a prognostic factor related to the treatment or not and if smoking level of the patients have any relationship to the SNPs' effect on the survival. Peripheral blood lymphocytes of 423 consecutive non-small cell lung cancer patients were examined: 245 of the patients received cisplatin combination chemotherapy and 178 received only conservative care. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
2
29
2
Order By: Relevance
“…However, conflicting results have been reported by other investigators, demonstrating that any copies of the A allele were associated with shorter survival in NSCLC patients (21)(22)(23). On the other hand, a few studies with larger sample size than ours have reported that ERCC1-C8092A polymorphism had no influence on survival in NSCLC patients (8,15). In the above-mentioned studies, the stage of the disease as well as the tumor histology, chemotherapy regimen, and race of the subjects were different.…”
Section: Discussioncontrasting
confidence: 67%
“…However, conflicting results have been reported by other investigators, demonstrating that any copies of the A allele were associated with shorter survival in NSCLC patients (21)(22)(23). On the other hand, a few studies with larger sample size than ours have reported that ERCC1-C8092A polymorphism had no influence on survival in NSCLC patients (8,15). In the above-mentioned studies, the stage of the disease as well as the tumor histology, chemotherapy regimen, and race of the subjects were different.…”
Section: Discussioncontrasting
confidence: 67%
“…For example, a case-control study showed the presence of a gene-smoking interaction with the ERCC1 polymorphism (5). This interaction was also observed in our recent study (6). Prognostic significance was observed only in those patients with non -small cell lung cancer who were heavy smokers (z50 pack-years; P = 0.03, using the log-rank test).…”
supporting
confidence: 83%
“…So, differences in ERCC1 expression may not affect the survival of women receiving platinum-based treatments. ERCC1 polymorphisms are also associated with response to treatment and overall survival in advanced NSCLC patients treated with platinum-based chemotherapy [43][44][45][46][47][48], though some authors have discordant results [49,50].…”
Section: Discussionmentioning
confidence: 99%